Experiencing the Digital News: The multiple dimensions of users’ experience in news media use - Omar, Bahiyah; Mustafa, Hasrina (SHS web of conferences)
The term media experience is seldom defined explicitly by communication and media scholars. Most often, it refers to media use and the feeling (such as enjoyment) resulted from the use. To fill this void, the present study turns to presence studies which espouse the idea of being there in mediated environment. As online news use involves a kind of mediated experience, this study adopts the existing measure of presence to determine the multiple dimensions of online news experience. A Principal Component Analysis (PCA) was used to establish the dimensions of the experience in this exploratory study. Four dimensions were extracted from the analysis: para-social interaction, transportation, absorption and social realism. The study found that online news users were experiencing beyond ordinary description; they interacted with the news, absorbed in the narrative world, and to certain extent felt that they were being transported into such world and also experienced the realism that the news stories tend to convey. Implications for understanding the experience in news media use from presence perspective are discussed.